Amsassia (calcareous alga) from the Lower Ordovician (Tremadocian) of western Newfoundland, and the biologic affinity and geologic history of the genus. (January 2022) - Lee, Dong-Jin; Elias, Robert J.; Pratt, Brian R.
Abstract: Modular coral-like fossils from Lower Ordovician (Tremadocian) thrombolitic mounds in the St. George Group of western Newfoundland were initially identified as Lichenaria and thought to include the earliest tabulate corals. They are here assigned to Amsassia terranovensis n. sp. and Amsassia ? sp. A from the Watts Bight Formation, and A . diversa n. sp. and Amsassia ? sp. B from the overlying Boat Harbour Formation. Amsassia terranovensis n. sp. and A . argentina from the Argentine Precordillera are the earliest representatives of the genus. Amsassia is considered to be a calcareous alga, possibly representing an extinct group of green algae. The genus originated and began to disperse in the Tremadocian, during the onset of the Great Ordovician Biodiversification Event, on the southern margin of Laurentia and the Cuyania Terrane. It inhabited small, shallow-marine reefal mounds constructed in association with microbes. The paleogeographic range of Amsassia expanded in the Middle Ordovician (Darriwilian) to include the Sino-Korean Block, as well as Laurentia, and its environmental range expanded to include non-reefal, open- and restricted-marine settings. Amsassia attained its greatest diversity and paleogeographic extent in the Late Ordovician (Sandbian–Katian), during the culmination of the Great Ordovician Biodiversification Event. Its range included the South China Block, Tarim Block, Kazakhstan, and Siberia, as well as the Sino-Korean Block and Laurentia, and its affinity for small microbial mounds continued during that time. In the latest Ordovician (Hirnantian), the diversity of Amsassia was reduced, its distribution was restricted to non-reefal environments in South China, and it finally disappeared during the end-Ordovician mass extinction. UUID: http://zoobank.org/ef0abb69-10a6-46de-8c78-d6ec7de185fe